Eosinophilic fasciitis - Vučinič Dugonik, Aleksandra (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
A 58-year-old woman was evaluated for disseminated scleroderma-like skin lesion which started on lateral aspects of the upper extremities and progressed rapidly, involving trunk and lower extremities. They first skin lesions appeared one month after she had started simvastatin therapy for hypercholesterolemia. Clinical and histopathological findings corresponded to the diagnosis eosinophilic fasciitis. Methylprednisolone 60 mg per day was started; simvastin was discontinued. After two weeks of therapy the patient became afebrile, arthalgic pains and edema of legs subsided, and skin lesions softened. The percentage of eosinophils dropped to normal. The eosinophilic fasciitis was possibly induced by the 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, simvastatin, an association that has been previously described.
Keywords: Drug therapy; Fasciitis; Scleroderma